Temporally ordered associations between type 2 diabetes and brain disorders – a Danish register-based cohort study - Theresa Wimberley; Henriette T. Horsdal; Isabell Brikell; Thomas M. Laursen; Aske Astrup; Giuseppe Fanelli; Janita Bralten; Geert Poelmans; Veerle Van Gils; Willemijn J. Jansen; Stephanie J. B. Vos; Valérie Bertaina-Anglade; et al. (BMC Psychiatry, 2022)
Abstract Background Type 2 diabetes mellitus (T2DM) is linked with several neurodegenerative and psychiatric disorders, either as a comorbid condition or as a risk factor. We aimed to expand the evidence by examining associations with a broad range of brain disorders (psychiatric and neurological disorders, excluding late-onset neurodegenerative disorders), while also accounting for the temporal order of T2DM and these brain disorders. Methods In a population-based cohort-study of 1,883,198 Danish citizens, born 1955–1984 and followed until end of 2016, we estimated associations between T2DM and 16 brain disorders first diagnosed between childhood and mid-adulthood. We calculated odds ratios (OR) and hazard ratios (HR) with 95% confidence intervals (CI) in temporally ordered analyses (brain disorder diagnosis after T2DM and vice versa), adjusted for sex, age, follow-up, birth year, and parental factors. Results A total of 67,660 (3.6%) of the study population were identified as T2DM cases after age 30 and by a mean age of 45 years (SD of 8 years). T2DM was associated with most psychiatric disorders. Strongest associations were seen with other (i.e. non-anorectic) eating disorders (OR [95% CI]: 2.64 [2.36–2.94]) and schizophrenia spectrum disorder (2.73 [2.63–2.84]). Among neurological disorders especially inflammatory brain diseases (1.73 [1.57–1.91]) and epilepsy (1.67 [1.60–1.75]) were associated with T2DM. Most associations remained in both directions in the temporally ordered analyses. For most psychiatric disorders, associations were strongest in females. Conclusions T2DM was associated with several psychiatric and neurological disorders, and most associations were consistently found for both temporal order of disorders. This suggests a shared etiology of T2DM and those brain disorders. This study can form the starting point for studies directed at further elucidating potential causal links between disorders and shared biological mechanisms.